Application of the Contextual Teaching and Learning (CTL) Learning Model with the Help of Quizizz as an Evaluation Media in Improving Problem Solving Ability - Nur Laila; Syarifah Rahmiza Muzana; Rina Mirdayanti (Jurnal Materi dan Pembelajaran Fisika, 2024)
Literacy and numeracy in physics are still lacking which is dominated by teachers and is always considered difficult by SMA Negeri 1 Blangkejeren students, The purpose of this study was to determine the Contextual Teaching and Learning (CTL) and Quizizz learning models can improve students' problem solving skills on momentum and impulse material. The method used in this research is the Quasy experiment method with a quantitative approach and the research design is Nonequivalent Control Group Design. This research was carried out by giving a pretest-posttest class. By cluster random sampling techniques, so the samples determined were class X. The number of samples per class is 27 students. The research measurement tools used in the study were RPP and LKPD that had been prepared containing several steps of the CTL learning model that were to be realized in the teaching and learning process as well as test questions to obtain data related to the results of students' problem-solving abilities. The tests that were prepared in the form of questions included 13 questions based on ability indicators based on Bloom's Taxonomy including C1 (understanding) to C5 (evaluating). The test data provided were the average pre-test and post-test scores CTL (Contextual Teaching and Learning) learning with Quizizz evaluation media provides better results than using conventional learning models, with game-shaped questions and scores making SMA Negeri 1 Blangkejeren students compete to get better scores.